Verbs and the verb: from morphology to discourse and back to the lexicon - Garrido, Joaquín; Maldonado, Concepción (Círculo de Lingüística Aplicada a la Comunicación, 2013)
This special issue on verbs shows that they continue to be a priviledged avenue of access to central questions of language, from morphology and the lexicon to discourse structure.